Literature Study: An Analysis of Islamic Culture During The Umayyah Period - Lubis, Nur Haflisma; Haidar Putra Daulay; Sholihah Titin Sumanti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The purpose of this research is to know more deeply about Islamic culture in the Umayyah period as reviewed from existing historical literature. This study adopts a descriptive qualitative approach with a focus on literature studies. The results of the study show that the Umayyah dynasty was founded by Muawiyah bin Abi Sufyan, this dynasty became the first caliphate after the time of Khulafaur Rashidin, lasting from 661 to 750 AD. During this reign, a monarchy system was implemented, which means that the appointment of the caliph took place based on the lineage or direct appointment of the previous caliph. Islamic Civilization History Education (SPI) requires effective learning methods to teach this material to students with various methods, such as storytelling, question and answer discussions, group work, and lectures as the main approach in SPI learning. The use of this varied method aims to increase students' involvement in the learning process, help them internalize historical values as well as understand the socio-political context that shapes Islamic civilization. Through this learning approach, students are expected not only to understand the history of the caliphate but also to be able to apply positive values, such as justice and wise leadership in their lives. Figures such as Umar bin Abdul Aziz, known for his justice, serve as an example for students to see how a wise leader can have a great influence on society.